2011
DOI: 10.1021/np2002435
|View full text |Cite
|
Sign up to set email alerts
|

Oleanane-Type Triterpenoids from the Leaves and Twigs of Fatsia polycarpa

Abstract: Seven new oleanane-type triterpenoids (1-7), named fatsicarpains A-G, and the known compounds 3α-hydroxyolean-11,13(18)-dien-28-oic acid (8) and 3α-hydroxyolean-11-en-28,13β-olide (9) were isolated from the leaves and twigs of Fatsia polycarpa on the basis of bioassay-guided fractionation. The structures of compounds 1-7 were elucidated through spectroscopic analyses and single-crystal X-ray crystallography of 1, 8, and 9. Cytotoxicity against HepG2 2.2.15 and AGS cells and antihepatitis B virus (HBV) and anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…The 1 H NMR spectrum of compound 3 displayed signals due to seven tertiary methyl groups at d H 1.10 (H-27), 1.06 (H-25), 1.05 (H-26), 0.99 (H-23 and 29), 0.92 (H-30) and 0.80 ppm (H-24). This indicated an oleanane structure of compound 3, which was confirmed by comparing the spectral data with those of related compounds (Cheng et al 2011;Lai et al 2012). 1 H NMR and 13 C NMR spectral data of compound 3 showed the absence of the olefinic bond signals and the appearance of a broad singlet at d H 3.03 ppm integrated for two protons and their corresponding carbon atoms, according to HSQC, displayed at d C 52.7 and 57.3 ppm ascribable for 11a,12a an epoxy group (Xue et al 2011).…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…The 1 H NMR spectrum of compound 3 displayed signals due to seven tertiary methyl groups at d H 1.10 (H-27), 1.06 (H-25), 1.05 (H-26), 0.99 (H-23 and 29), 0.92 (H-30) and 0.80 ppm (H-24). This indicated an oleanane structure of compound 3, which was confirmed by comparing the spectral data with those of related compounds (Cheng et al 2011;Lai et al 2012). 1 H NMR and 13 C NMR spectral data of compound 3 showed the absence of the olefinic bond signals and the appearance of a broad singlet at d H 3.03 ppm integrated for two protons and their corresponding carbon atoms, according to HSQC, displayed at d C 52.7 and 57.3 ppm ascribable for 11a,12a an epoxy group (Xue et al 2011).…”
Section: Resultssupporting
confidence: 58%
“…The olefinic bond at C-11/C-12 was evident from the long-range correlations between each of H-11/C-10, C-8, and C-13, and H-12/C-9, C-13, and C-14 in the HMBC spectrum. From the aforementioned discussion and by comparison with the spectral data of the related compounds (Pereda-Miranda & Delgado 1990;Cheng et al 2011;Huang et al 2012), compound 2 could be identified as 3b-hydroxy-urs-11-en-13b,28-olide which is a newly isolated compound.…”
Section: Resultsmentioning
confidence: 98%
“…There are three species in the genus of Fatsia (belonging to the Araliaceae family), that is, Fatsia polycarpa Hayata, an evergreen shrub endemic to Taiwan, Fatsia japonica, and Fatsia oligocarpela , originated from Japan and Bonin Islands, respectively [1]. F. japonica and F. polycarpa have been used as an herbal medicine in Japan and in Taiwan in treating diseases, such as coughing, ankylosing spondylitis, osteoarthritis, rheumatism, rheumatoid arthritis and tendinitis, and in blood circulation improvement [1, 2].…”
Section: Introductionmentioning
confidence: 99%
“…F. japonica and F. polycarpa have been used as an herbal medicine in Japan and in Taiwan in treating diseases, such as coughing, ankylosing spondylitis, osteoarthritis, rheumatism, rheumatoid arthritis and tendinitis, and in blood circulation improvement [1, 2]. Nonetheless, the therapeutic activity of F. polycarpa has seldom been scientifically investigated and the bioactive constituents from these plants are not clear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation